2011
DOI: 10.1159/000333477
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Programming of Hypertension in the Rat: Effect of Postnatal Rearing

Abstract: Background/Aims: Dietary protein deprivation during pregnancy causes hypertension in offspring when they become adults. This study examined if postnatal rearing had an effect on blood pressure and glomerular number in male rats whose mothers were fed either a control diet or a low protein diet. Methods: Neonates were cross fostered at 1 day of age to a different mother. After birth, all nursing and weaned rats were fed a control diet. Blood pressure and glomerular number were measured in adult offspring. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…Rats in the 20% to 6% group and 6% to 6% group did not gain weight at the same rate as rats in the 6% to 20% group and 20% to 20% group, which was still apparent in the present study when rats were studied at 3 and 17 mo of age. We also found that optimizing the postnatal environment by cross-fostering neonatal pups on day 1 of life whose mothers were fed a low-protein diet during pregnancy to a mother that was fed a 20% control diet during pregnancy and while nursing (6% to 20% group) prevented the reduction in nephron number (14,36). Only 6% to 6% rats had a decrease in nephron number (36).…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Rats in the 20% to 6% group and 6% to 6% group did not gain weight at the same rate as rats in the 6% to 20% group and 20% to 20% group, which was still apparent in the present study when rats were studied at 3 and 17 mo of age. We also found that optimizing the postnatal environment by cross-fostering neonatal pups on day 1 of life whose mothers were fed a low-protein diet during pregnancy to a mother that was fed a 20% control diet during pregnancy and while nursing (6% to 20% group) prevented the reduction in nephron number (14,36). Only 6% to 6% rats had a decrease in nephron number (36).…”
Section: Discussionmentioning
confidence: 75%
“…The effect of prenatal maternal insults on the fetus are not set in stone and can be modified by changes in the early postnatal environment (5,14,44). We have previously examined the effect of cross-fostering rats whose mothers were fed a 6% protein diet and a 20% protein diet during pregnancy and while nursing (36).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…34 However, unlike the present study, all nursing mothers were placed on a 20% protein diet after birth. The neonates from 20% rats fostered to a mother that was fed a 6% protein diet during pregnancy but was then fed a 20% protein diet while nursing did not have hypertension or a reduction in nephron number.…”
Section: Discussionmentioning
confidence: 87%